2020
DOI: 10.1002/jgc4.1338
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic counseling on women's grief and coping following termination of pregnancy for fetal anomaly

Abstract: Pregnancy termination for fetal anomaly (TFA) is a unique experience that can cause women to develop long‐term complicated grief. Although a woman's experience with her healthcare providers has been previously identified as an important factor in coping, studies have shown that many women report their health care as lacking to some extent. Given the overlap in women's needs and the practice scope of a genetic counselor (GC), this study aimed to examine how genetic counseling may impact coping and explore women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Training in grief and loss is considered an important aspect of genetic counselling practice [ 36 ]. A recent study explored the role of genetic counsellors in mitigating complex or prolonged grief following termination of pregnancy for fetal anomalies and identified a major role for genetic counsellors in facilitating adaptive coping [ 37 ]. Future research aiming to gain a better understanding of grief related to reproductive losses in the setting of RGCS will ensure that health providers can provide support and promote effective coping in increased risk couples.…”
Section: Discussionmentioning
confidence: 99%
“…Training in grief and loss is considered an important aspect of genetic counselling practice [ 36 ]. A recent study explored the role of genetic counsellors in mitigating complex or prolonged grief following termination of pregnancy for fetal anomalies and identified a major role for genetic counsellors in facilitating adaptive coping [ 37 ]. Future research aiming to gain a better understanding of grief related to reproductive losses in the setting of RGCS will ensure that health providers can provide support and promote effective coping in increased risk couples.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to an average pregnant woman or birthing person, they made more visits to medical institutions and even requested for extra checkups, saw various healthcare professionals, depended more heavily on healthcare professionals for informational and emotional support, and had a more therapeutic physician-patient relationship (Lafarge et al, 2013(Lafarge et al, , 2019Rillstone, 1999). Additionally, parents in two studies reported utilising local and online pregnancy support groups to share their experiences, seek connection, reassurance and support from 'credible' parents, and manage plans while coping with the pain of a difficult pregnancy (Rillstone, 1999;Smith et al, 2021).…”
Section: Managing Expectations and Staying Guarded During A Future Pr...mentioning
confidence: 99%
“…Health professionals should be aware of the potential for compounding effects during the prenatal diagnosis process and identify individuals/ couples that may require a referral to a psychologist, as non-medical interventions can provide coping strategies and support (Bailey et al, 2015;Frederiksen et al, 2017). Genetic Counselors can provide emotional support to translocation carriers and their partners during this time to facilitate adaptive coping (Smith et al, 2021).…”
Section: Impacts Of Being a Carriermentioning
confidence: 99%